Linking Corporate Risk Disclosure Practices with Firm-Specific Characteristics in Saudi Arabia - Norsiah Ahmad; Omer Saeed Habtoor; Nor Raihan Mohamad; Mohd Hassan Che Haat (Master in Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2017)
This study explores Corporate Risk Disclosure practices (CRD) in the annual reports of Saudi (non-financial) listed companies and investigates the relationship between the Saudi firm-specific characteristics and the level of such practices. Using content analysis of a sample of 307 company-year observations over the period of 2008-2011, the results indicate that Saudi Arabia provides a moderate level of CRD among the developed and developing countries. However, the content of this CRD is found to be of a low quality, by including non-financial, qualitative, neutral, or non-time-specific information. In addition, the unbalanced panel regression analysis shows a significant positive influence of firm size and audit firm size on the level of CRD. This indicates that Saudi companies which disclose higher risk-related information are those characterised by their larger size, and are audited by the Big 4 audit firms. This study contributes to the risk literature by providing an initial understanding of the CRD practices and their variations in light of the firm-specific characteristics in emerging markets in general and Arab countries in particular..